ACTIVITY OF WATER EXTRACT OF INDIAN PENNYWORT HERB (CENTELLA ASIATICA (L.) URBAN) AND ITS FRACTIONS ON MEMORY IN ANIMAL MODEL OF ALZHEIMERâS DISEASE - Zahra Amatullah, Anita
Alzheimer's disease (AD) is a degenerative brain disorder which has a quite large prevalence. Indian pennywort is plant of the Apiaceae family known to have an effect on learning and memory process. This study was aimed to develop an animal model of AD induced by intracerebroventricular alloxan and to test the activity of aqueous extract and fraction of Indian pennywort’s herb on memory function. Tests for memory performance were carried out using water maze and Y-maze apparatus with escape latency time (ELT) as parameter, performed on days 1, 3, 5, 7, 14 and 21 of treatment. ELT or latency time is the time that mice needed to climb the platform hidden in the water maze and to find food in one arm of Y-maze. At the end of the experiment representative mice from each group were sacrificed for brain histological examination and measurement of acetylcholinesterase activity. Results showed that ELT values of positive control received only icv alloxan were significantly different from baseline and naive group both in the water maze and the Y-maze (p<0.01). On the first day of testing, there is a significant difference (p<0.01) between groups FA32 (mice received alloxan 5.6 mg/kg bw and water fraction of indian pennywort 32 mg/kg bw), FA56 (mice received alloxan 5.6 mg/kg bw and water fraction of indian pennywort 56 mg/kg bw), and EA280 (mice received alloxan 5.6 mg/kg bw and water extract of indian pennywort 280 mg/kg bw) compared to positive control group on water maze, whereas the Y-maze was not significantly different among all treatment groups compared to positive control group. On the 3rd day of testing, there were significant difference (p<0.01) among all treatment groups, except FEA56 (mice received alloxan 5.6 mg/kg bw and ethyl acetat fraction of indian pennywort 56 mg/kg bw), compared to positive control of the water maze, while the Ymaze, a significant difference (p<0.01) only indicated by FA56 group, EA280, EA420 (mice received alloxan 5.6 mg/kg bw and water extract of indian pennywort 420 mg/kg bw) compared to positive control. On day 5 up to 21 after alloxan treatment, there were significant differences (p<0.01) among all treatment groups compared to the positive control group both in the water maze and the Y-maze. Brain histological observations revealed larger number of necrotic neuroglia and pyramid cells in positive control group compared to naive group and all treatment group. Based on the results of measurements of the activity of the enzyme acetylcholinesterase, all treatment groups, except FA56, showed higher enzyme activity than the positive control which indicates the high concentration of acetylcholine in the brain. The results show that intracerebroventricullarly alloxan 5.6 mg/kg bw can be utilized as Alzheimer-inducing agent in mice. In all parameters, both the water extract and fraction of indian pennywort herb had good activity against murine models of memory in Alzheimer's disease where the best result was shown by the water fraction of indian pennywort at dose of 32 mg / kg bw.